Uncommon testicular metastasis of a primary neuroendocrine tumour of the lung - Birker, Ingrid L.; van der Zee, Johan A.; Keizer, Karin M. (Canadian Urological Association Journal, 2013)
A 52-year-old male presented with an asymptomatic palpable mass of the right testicle. Ultrasound confirmed the presence of a testicular tumour and a hemicastration was performed. None of the testis cancer-related tumour markers were elevated and histological findings revealed a neuroendocrine carcinoma, possibly a metastasis from another primary site. The radiological findings showed a lesion in the lung, and a positron emission tomography (PET)-scan was made. The PET scan revealed an increased fluorodeoxyglucose (FDG) uptake in the pulmonary lesion. It also showed lymphatic and hepatic metastases. The patient had no complaints besides a palpable testicular mass and was diagnosed with a cT1aN3M1b neuroendocrine carcinoma of the lower left field of the lung, stage IV. To our knowledge, the presentation of testicular metastasis of a neuroendocrine carcinoma of the lung has not been described in the literature. No curative options were available and the patient is being treated with salvage chemotherapy.